Translation and Validation of a Chinese Version of the Mindfulness in Parenting Questionnaire (MIPQ) - Wu, Lei; Buchanan, Heather; Zhao, Yaping; Wang, Ping; Zhan, Zhao; Zhao, Boyao; Fan, Bijuan (Frontiers in Psychology, 2019)
Objective: To translate the Mindfulness in Parenting Questionnaire (MIPQ) into Standard Mandarin and then explore the reliability and validity of this newly translated measure in a large sample of Chinese middle school parents. Methods: We translated the MIPQ using the forward-backward method and pilot tested it on a sample of parents of adolescents (aged 12–16 years) in China. Following minor modifications, 1057 Chinese parents (Mothers or Fathers) in two middle schools (one in the North and one in the South of China) completed the translated Chinese Mindfulness in Parenting Questionnaire (C-MIPQ). To determine test-retest reliability 121 participants completed the C-MIPQ again 2 weeks later. In order to test convergent validity, 395 participants completed the Mindful Attention and Awareness Scale (MAAS), Parenting Styles and Dimensions Questionnaire-Short Version (PSDQ-short) and the Interpersonal Mindfulness in Parenting Scale (IM-P). The Chinese Perceived Stress Scale (CPSS), Beck Depression Scale (BDI-13), and socioeconomic status (SES) were completed in order to test discriminant validity. Results: Confirmatory factor analysis showed that the two-factor model indicated in the original study was a good fit. The total score of the scale and the scores of the two dimensions (‘Mindful discipline’ and ‘Being in the moment with the child’) were significantly positively correlated with the total score of the MAAS, IM-P and the authoritative parenting style in the PSDQ-short, demonstrating convergent validity. Discriminant validity was established as there was no difference in C-MIPQ sub-scale scores across any of the SES variables except for levels of education (parents with higher education had higher scores on the ‘being in the moment with the child’ subscale). In addition, the C-MIPQ was negatively related to stress and depression. Cronbach’s alpha of the total scale was 0.93 (and 0.88, 0.89 for the two dimensions of the C-MIPQ) indicating excellent internal consistency. Test-retest reliability was good (intra-class correlation of 0.83). Conclusion: This study is the first step toward establishing the psychometric properties of the C-MIPQ for measuring mindful parenting in parents of adolescents aged 12–16 years; additional studies will be needed in order to test this further.